Overexpression of the HcPT1.1 transporter in Hebeloma cylindrosporum alters the phosphorus accumulation of Pinus pinaster and the distribution of HcPT2 in ectomycorrhizae - Amenc, Laurie; Becquer, Adeline; Trives-Segura, Carlos; Zimmermann, Sabine D.; Garcia, Kevin; Plassard, Claude (Frontiers in Plant Science, 2023)
Ectomycorrhizal (ECM) fungi are associated with the roots of woody plants in temperate and boreal forests and help them to acquire water and nutrients, particularly phosphorus (P). However, the molecular mechanisms responsible for the transfer of P from the fungus to the plant in ectomycorrhizae are still poorly understood. In the model association between the ECM fungus Hebeloma cylindrosporum and its host plant Pinus pinaster, we have shown that the fungus, which possesses three H+:Pi symporters (HcPT1.1, HcPT1.2 and HcPT2), expresses mainly HcPT1.1 and HcPT2 in the extraradical and intraradical hyphae of ectomycorrhizae to transport P from the soil to colonized roots. The present study focuses on the role of the HcPT1.1 protein in plant P nutrition, in function of P availability. We artificially overexpressed this P transporter by fungal Agrotransformation and investigated the effect of the different lines, wild-type and transformed ones, on plant P accumulation, the distribution of HcPT1.1 and HcPT2 proteins in ectomycorrhizae by immunolocalization, and 32P efflux in an experimental system mimicking intraradical hyphae. Surprisingly, we showed that plants interacting with transgenic fungal lines overexpressing HcPT1.1 did not accumulate more P in their shoots than plants colonized with the control ones. Although the overexpression of HcPT1.1 did not affect the expression levels of the other two P transporters in pure cultures, it induced a strong reduction in HcPT2 proteins in ectomycorrhizae, particularly in intraradical hyphae, but still improved the P status of host plant shoots compared with non-mycorrhizal plants. Finally, 32P efflux from hyphae was higher in lines overexpressing HcPT1.1 than in the control ones. These results suggest that a tight regulation and/or a functional redundancy between the H+:Pi symporters of H. cylindrosporum might exist to ensure a sustainable P delivery to P. pinaster roots.